Self-supporting electrode based on one-dimensional conductive material and preparation method thereof

By directly preparing self-supporting electrodes using one-dimensional conductive materials and electrode active materials such as lithium manganate, the problem of large gap between the actual capacity and the ideal capacity of existing lithium-ion batteries and low efficiency in the first circle is solved, and more efficient battery capacity utilization and lower preparation costs are achieved.

CN119764346APending Publication Date: 2025-04-04SHAOXING INST OF NEW ENERGY & MOLECULAR ENG SHANGHAI JIAO TONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411769865.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There is a big gap between the actual capacity of existing lithium-ion batteries and the ideal capacity. The first round is not efficient and the need to add a large amount of conductive materials leads to an increase in costs.

Method used

Self-supporting electrodes are directly prepared using one-dimensional conductive materials and electrode active substances. By mixing one-dimensional conductive materials such as carbon nanotubes with electrode active substances such as lithium manganate in proportion, and after freezing and freeze-drying, a structure inside the electrode is prepared with the positive electrode active substance itself and carbon nanotubes.

Benefits of technology

The actual specific capacity of lithium manganate is significantly improved, making it closer to the ideal specific capacity, improving the conductivity and charge and discharge performance of the electrode, and reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764346A_ABST
    Figure CN119764346A_ABST
Patent Text Reader

Abstract

The invention discloses a self-supporting electrode based on a one-dimensional conductive material and a preparation method thereof, and relates to the technical field of lithium ion batteries, and the preparation method comprises the following steps: S1, mixing the one-dimensional conductive material, an electrode active material and bacterial cellulose according to a ratio, and uniformly dispersing; s2, freezing the materials mixed in the step S1 at the temperature of-60 DEG C to-40 DEG C for 6-24 hours; and S3, performing freeze drying treatment on the material treated in the step S2 at the temperature of-60 DEG C to-40 DEG C for 48-64 hours, and directly preparing an electrode plate after the treatment. Compared with the preparation of the traditional coated lithium ion battery electrode, the preparation method has the advantages that the preparation process is simpler, the influence factors are fewer, and the preparation method has important guiding significance on the industrial production of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a self-supporting electrode based on a one-dimensional conductive material and a preparation method thereof. Background Art

[0002] Existing lithium-ion batteries generally use aluminum foil as a carrier of electrode materials, such as CN116854149A, CN115995538A, and CN118553855A. However, the actual capacity of lithium-ion batteries prepared by this method is often quite different from the ideal capacity of the electrode active material. At the same time, the first-cycle efficiency of the battery cannot always reach a high value. In addition, some batteries often need to add more conductive materials to enable the active material to exert its performance, such as CN118270846A, resulting in an active material percentage of less than 90% or even 80%, which will lead to higher costs.

[0003] In addition, in a method for preparing a graphene-lithium manganate composite membrane electrode for lithium extraction disclosed in CN118270846A: an aqueous solution of graphene oxide and lithium manganate powder are assembled together along the growth direction of ice crystals under the action of freeze-induced phase separation (ice template method), and a one-dimensional additive with mechanical strength connects the two-dimensional graphene oxide sheets to form a three-dimensional aerogel with vertically arranged channels; the oxygen-containing functional groups of the aerogel are then removed by reduction treatment, thereby further improving the flexibility and conductivity of the material, and obtaining a highly conductive flexible composite membrane electrode without an external current collector or binder.

[0004] Since this type of electrode uses a two-dimensional conductive material, the mass transfer efficiency of the two-dimensional conductive material is very low due to its layered structure, which is not conducive to the battery's charging and discharging process.

[0005] Therefore, developing a lithium-ion battery with an ideal capacity and high initial efficiency that can utilize active materials more efficiently and at a low cost is of great significance to promoting the development of the lithium-ion battery field. Summary of the invention

[0006] In view of the above technical deficiencies, the present invention provides a method for preparing a self-supporting electrode based on a one-dimensional conductive material with higher efficiency.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A method for preparing a self-supporting electrode based on a one-dimensional conductive material comprises the following steps:

[0009] S1. Mix the one-dimensional conductive material, the electrode active substance and the bacterial cellulose in proportion to make them dispersed evenly; the mass percentages of the one-dimensional conductive material, the electrode active substance and the bacterial cellulose are as follows:

[0010] Positive electrode active material 90%-98%

[0011] One-dimensional conductive materials 1%-10%

[0012] Bacterial cellulose 1%-10%

[0013] S2, freezing the mixed materials in S1 at a temperature of -60°C to -40°C for 6 to 24 hours;

[0014] S3. The material treated in S2 is freeze-dried at a temperature of -60°C to -40°C for 48 to 64 hours. After the treatment, the material can be directly sliced.

[0015] Further settings are:

[0016] In S1, the positive electrode active material is LiMn2O4.

[0017] In S1, the one-dimensional conductive material is any one of nanowires, nanofibers or carbon nanotubes or a combination of two thereof, preferably carbon nanotubes.

[0018] In S1, the mixing may be carried out by any one or more of stirring and ultrasonic treatment.

[0019] In S2, the freezing treatment is carried out in a low-temperature refrigerator, preferably at a freezing treatment temperature of -50°C for 12 hours.

[0020] In S3, the freeze-drying treatment is carried out in a vacuum freeze dryer, preferably at a freeze-drying temperature of -50°C for 48 hours.

[0021] In S3, after the freeze-drying process is completed, the sample is cut into circular electrodes with a diameter of 12 mm.

[0022] The present invention also provides a self-supporting electrode based on a one-dimensional conductive material prepared by the above method, characterized in that the interior of the electrode is supported by the positive electrode active material itself and the carbon nanotubes coated on its surface, and the positive electrode active material accounts for more than 95% of the electrode.

[0023] Another object of the present invention is to provide a self-supporting electrode based on one-dimensional conductive material for use in lithium ion batteries.

[0024] The mechanism of action of the present invention is as follows:

[0025] The inventor has found through research that the existing preparation process uses a method of coating a slurry containing active substances on aluminum foil or other current collectors. The resulting battery capacity is not only related to the active substances, but also to the dispersant used due to the adhesion effect between the coating and the current collector. Since the dispersant is a poor conductor of electrons, it will limit the electron movement ability of the conductive coating, thereby limiting the overall electrochemical system rate performance of the battery. At the same time, the conductive materials used in most existing electrodes are two-dimensional structures, which are prone to interlayer stacking, resulting in a reduction in specific surface area and active sites, and reducing the actual specific capacity of the material. In addition, due to the influence of its layered structure, the interlayer electron transfer efficiency of the two-dimensional conductive material is usually low, which is not conducive to the battery's charge and discharge process.

[0026] The present invention uses one-dimensional conductive materials and active materials to directly prepare self-supporting electrodes, without the need for aluminum foil or other current collectors. The one-dimensional conductive material, as a one-dimensional structural material, increases the contact area with the electrode material, greatly improving the conductivity of the electrode. The interlayer stacking effect of two-dimensional conductive materials (such as graphene, transition metal sulfides, etc.) is avoided. At the same time, the self-supporting electrode based on one-dimensional conductive materials prepared by the present invention is in direct contact with the battery, reducing the influence of the dispersant in the traditional battery.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] (1) Compared with the existing process, the present invention significantly improves the actual specific capacity of lithium manganese oxide, making it closer to its ideal specific capacity. The one-dimensional conductive material carbon nanotubes can effectively avoid the poor mass transfer and interlayer stacking effect of the two-dimensional conductive material, greatly improve the internal ion dynamics of the electrode, and effectively improve the battery capacity.

[0029] (2) Compared with the preparation of lithium-ion battery electrodes by traditional coating methods, the preparation process of the present invention is simpler and has fewer influencing factors, which has important guiding significance for the industrial production of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the self-supporting electrode based on one-dimensional conductive material prepared in Example 1.

[0031] Figure 2 Thermogravimetric test results of the self-supporting electrode based on one-dimensional conductive material prepared in Example 1.

[0032] Figure 3 Comparison of charge and discharge tests between a conventional coated electrode and a self-supporting electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described in combination with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the following examples, unless otherwise specified, the raw materials and equipment used in the examples are all known or commercially available products.

[0035] Example 1

[0036] A self-supporting electrode based on a one-dimensional conductive material, comprising the following components:

[0037] Electrode active material LiMn2O4 2.42g

[0038] 20g of 0.2% carbon nanotube aqueous solution

[0039] 4g of bacterial cellulose aqueous solution with a mass concentration of 1%

[0040] The preparation method is as follows:

[0041] S1, stirring and ultrasonicating the carbon nanotube aqueous solution, the electrode active material LiMn2O4 and the bacterial cellulose aqueous solution to make them uniformly dispersed;

[0042] S2, put the mixed materials in S1 into a low-temperature refrigerator for freezing treatment, the freezing treatment temperature is -50°C, and the time is 12 hours;

[0043] S3. The material frozen in S2 is fully freeze-dried in a vacuum freeze dryer at a temperature of -50°C for 48 hours. After the freeze-drying process, the obtained sample is cut into circular electrodes with a diameter of 12 mm.

[0044] Product Confirmation:

[0045] See also Figure 1 The figure shows a scanning electron microscope image of a self-supporting electrode based on a one-dimensional conductive material prepared in Example 1, showing the detailed internal structure of the self-supporting electrode. Figure 1 It can be seen that the interior of the electrode is supported by LMO itself and the carbon nanotubes coated on its surface, which confirms that the composite electrode has a self-supporting structure based on one-dimensional conductive materials.

[0046] Figure 2 Thermogravimetric test results of the self-supporting electrode based on one-dimensional conductive material prepared in Example 1. Figure 2It can be seen that: with the increase of temperature, the weight of the electrode gradually decreases. From 200℃ to 700℃, the bacterial cellulose and carbon nanotubes gradually decrease. After 700 degrees Celsius, the mass percentage remains unchanged, indicating that the bacterial cellulose and carbon nanotubes have completely disappeared, leaving only lithium manganese oxide, indicating that the active substance lithium manganese oxide accounts for 96.85% of the composite electrode.

[0047] Example 2

[0048] The preparation method is the same as that of Example 1, except that the formula composition of the self-supporting electrode is adjusted to:

[0049] Electrode active material LiMn2O4 4.92g

[0050] 20g of 0.2% carbon nanotube aqueous solution

[0051] 4g of bacterial cellulose aqueous solution with a mass concentration of 1%

[0052] Example 3

[0053] The preparation method is the same as that of Example 1, except that the formula composition of the self-supporting electrode is adjusted to:

[0054] Electrode active material LiMn2O4 0.72g

[0055] 20g of 0.2% carbon nanotube aqueous solution

[0056] 4g of bacterial cellulose aqueous solution with a mass concentration of 1%

[0057] Example 4

[0058] The preparation method is the same as that of Example 1, except that the formula composition of the self-supporting electrode is adjusted to:

[0059] Electrode active material LiMn2O4 0.5g

[0060] 20g of 0.2% carbon nanotube aqueous solution

[0061] 4g of bacterial cellulose aqueous solution with a mass concentration of 1%

[0062] Example 5

[0063] The preparation method is the same as that of Example 1, except that the formula composition of the self-supporting electrode is adjusted to:

[0064] Electrode active material LiMn2O4 2.8g

[0065] 20g of 0.2% carbon nanotube aqueous solution

[0066] 4g of bacterial cellulose aqueous solution with a mass concentration of 1%

[0067] Example 6

[0068] The preparation method is the same as that of Example 1, except that the formula composition of the self-supporting electrode is adjusted to:

[0069] Electrode active material LiMn2O4 1.52g

[0070] 20g of 0.2% carbon nanotube aqueous solution

[0071] 4g of bacterial cellulose aqueous solution with a mass concentration of 1%

[0072] Comparative Example 1

[0073] The same formula as in Example 1 is used, except that the electrode is prepared by a traditional coating method. The preparation method is as follows:

[0074] S1, stirring and ultrasonicating the carbon nanotubes, the electrode active material LiMn2O4 and the bacterial cellulose to make them uniformly dispersed;

[0075] S2. Apply the slurry stirred evenly in step S1 onto a conventional current collector aluminum foil, and then prepare a conventional coated electrode by vacuum drying.

[0076] Comparative Example 2

[0077] The same formula as in Example 2 is used, except that a conventional coated electrode is prepared by the method described in Comparative Example 1.

[0078] Comparative Example 3

[0079] The same formula as in Example 3 is used, except that a conventional coated electrode is prepared by the method described in Comparative Example 1.

[0080] Comparative Example 4

[0081] The same formula as in Example 4 is used, except that a conventional coated electrode is prepared by the method described in Comparative Example 1.

[0082] Comparative Example 5

[0083] The same formula as in Example 5 is used, except that a conventional coated electrode is prepared by the method described in Comparative Example 1.

[0084] Comparative Example 6

[0085] The same formula as in Example 6 is used, except that a conventional coated electrode is prepared by the method described in Comparative Example 1.

[0086] Performance Test:

[0087] At the same temperature and humidity, the self-supporting electrodes based on one-dimensional conductive materials prepared in Examples 1-6 and the traditional coated electrodes prepared in Comparative Examples 1-6 were respectively prepared into button batteries according to the same assembly process, and the battery capacity was tested. The test results are listed in Table 1.

[0088] Assemble button cells: The battery used for the test is CR2016 button type. The prepared electrode sheet is taken as the positive electrode and transferred to a glove box filled with Ar (water <1ppm, oxygen <1ppm). At the same time, the lithium sheet is used as the counter electrode, the electrolyte is 1MLiPF6 EC:DME:EMC solution plus 5wt% FEC mixed solution as the electrolyte, and Celgard is used as the separator to make a CR2016 button cell.

[0089] Test method: The test was carried out using the Xinwei charging and discharging platform, and the test conditions were 20℃, 0.2C, 3V-4.35V constant current charging and discharging test.

[0090] Test results:

[0091] Table 1. Battery capacity test results

[0092]

[0093] analyze:

[0094] (1) Combined with Table 1, Figure 3 As shown, the charge and discharge test comparison between the conventional coated electrode and the self-supporting electrode prepared by the embodiment of the present invention is as follows: the charge and discharge specific capacity of the self-supporting electrode prepared by the present invention is 125mAh / g, while the conventional coated electrode is 110mAh / g, and the charge and discharge specific capacity of the self-supporting electrode is significantly increased by 13.6%, indicating that the self-supporting electrode has better charge and discharge performance. This shows that compared with the existing process, the present invention significantly improves the actual specific capacity of lithium manganese oxide, making it closer to its own ideal specific capacity. The one-dimensional conductive material carbon nanotube can effectively avoid the poor mass transfer of the two-dimensional conductive material and the interlayer stacking effect, greatly improving the internal ion dynamics of the electrode and effectively improving the battery capacity.

[0095] (2) By comparing Examples 1-6, it can be seen that as the mass percentage of lithium manganese oxide in the self-supporting electrode increases, the product performance gradually increases until it reaches a peak of 125 mAh / g, and then the product performance decreases as the mass percentage of lithium manganese oxide increases.

[0096] Summarize:

[0097] The present invention provides a method for a self-supporting electrode based on a one-dimensional conductive material, which can effectively improve the capacity utilization of the positive electrode active material under the same material ratio, so that its actual capacity is closer to the ideal capacity of the active material. It is explained that the self-supporting electrode prepared based on the one-dimensional conductive material has the advantages of a one-dimensional structural material, which increases the contact area with the electrode material and greatly improves the conductivity of the electrode. The interlayer stacking effect of two-dimensional conductive materials (such as graphene, transition metal sulfides, etc.) is avoided, and the influence of their layered structure is avoided. Under the same or even better performance data, the self-supporting electrode has a simpler and easier to control preparation process, which has important guiding significance for the industrial production of batteries.

Claims

1. A method for preparing a self-supporting electrode based on a one-dimensional conductive material, characterized in that: The following steps are involved: S1. Mix the one-dimensional conductive material, the electrode active substance and the bacterial cellulose in proportion to make them dispersed evenly; the mass percentages of the one-dimensional conductive material, the electrode active substance and the bacterial cellulose are as follows: Positive electrode active material 90%-98% One-dimensional conductive materials 1%-10% Bacterial cellulose 1%-10% S2, freezing the mixed materials in S1 at a temperature of -60°C to -40°C for 6 to 24 hours; S3. The material treated in S2 is freeze-dried at a temperature of -60°C to -40°C for 48 to 64 hours. After the treatment, the material can be directly made into electrode sheets.

2. The method for preparing a self-supporting electrode based on a one-dimensional conductive material according to claim 1, characterized in that: In S1, the positive electrode active material is LiMn2O4.

3. The method for preparing a self-supporting electrode based on a one-dimensional conductive material according to claim 1, characterized in that: In S1, the one-dimensional conductive material is any one of nanowires, nanofibers or carbon nanotubes, or a combination of two thereof.

4. The method for preparing a self-supporting electrode based on a one-dimensional conductive material according to claim 1, characterized in that: In S1, the one-dimensional conductive material is a carbon nanotube.

5. The method for preparing a self-supporting electrode based on a one-dimensional conductive material according to claim 1, characterized in that: In S1, the mixing is carried out by any one or more of stirring and ultrasonic treatment.

6. The method for preparing a self-supporting electrode based on a one-dimensional conductive material according to claim 1, characterized in that: In S2, the freezing treatment is carried out in a low-temperature refrigerator at a freezing temperature of -50°C for 12 hours.

7. The method for preparing a self-supporting electrode based on a one-dimensional conductive material according to claim 1, characterized in that: In S3, the freeze-drying treatment is carried out in a vacuum freeze dryer at a temperature of -50°C for 48 hours.

8. The method for preparing a self-supporting electrode based on a one-dimensional conductive material according to claim 1, characterized in that: In S3, after the freeze-drying process is completed, the sample is cut into circular electrodes with a diameter of 12 mm.

9. A self-supporting electrode based on a one-dimensional conductive material prepared by the method of claim 1, characterized in that: The interior of the electrode is supported by the positive electrode active material itself and the carbon nanotubes coated on its surface. The positive electrode active material accounts for more than 95% of the electrode.

10. Use of a self-supporting electrode based on a one-dimensional conductive material prepared by the method of claim 1 in a lithium ion battery.

Citation Information

Patent Citations

  • Graphene-lithium manganate composite membrane electrode for extracting lithium as well as preparation method and application of graphene-lithium manganate composite membrane electrode

    CN118270846A

  • Preparation method of three-dimensional porous composite pole piece for flexible lithium ion battery

    CN107742695A

  • Nanocellulose-silicon-graphite micron sheet flexible electrode material and preparation method and application thereof,

    CN110581267A

  • High-performance lithium ion battery self-supporting polymer thick pole piece and preparation method thereof

    CN114388745A